2015
DOI: 10.4025/actascihealthsci.v37i1.24512
|View full text |Cite
|
Sign up to set email alerts
|

<b>Effects of hygiene guidance associated or not to provision of hygiene devices on habits of denture wearers

Abstract: Appropriate hygiene of dentures contributes to the maintenance of oral and systemic health. However, most of denture wearers had never been instructed on how to perform daily oral/denture care. The purpose of this study is to investigate the influence of a guidance material associated or not to the provision of hygiene devices and its effect on the habits of denture wearers. Forty-eight complete denture wearers were randomly divided into three groups. Group N received no guidance on how to clean and wear their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…The effects of educational intervention also mirror those improvements seen within the primary care audit by Mylonas et al and highlights the positive effects of patient education on the subsequent quality of the denture hygiene. 2,5,14 These results differ from those of Burnett et al in 1993, who found that after six months of educational intervention -written and verbal -there was no change in the denture cleaning habits of their subject group. Conversely, it has been demonstrated that illustrated denture instruction manuals and frequent recall intervals -with denture hygiene and oral hygiene reinforcement -aids in improving denture and oral hygiene habits, and can therefore be recommended.…”
Section: -6contrasting
confidence: 57%
See 3 more Smart Citations
“…The effects of educational intervention also mirror those improvements seen within the primary care audit by Mylonas et al and highlights the positive effects of patient education on the subsequent quality of the denture hygiene. 2,5,14 These results differ from those of Burnett et al in 1993, who found that after six months of educational intervention -written and verbal -there was no change in the denture cleaning habits of their subject group. Conversely, it has been demonstrated that illustrated denture instruction manuals and frequent recall intervals -with denture hygiene and oral hygiene reinforcement -aids in improving denture and oral hygiene habits, and can therefore be recommended.…”
Section: -6contrasting
confidence: 57%
“…2,5,14,20 While the baseline results for patients in this audit was slightly better than for those seen in primary dental care, the reasons for the inadequacy of patient denture hygiene were similar: lack of standardisation of denture care instructions, and lack of evidence that denture hygiene instructions were previously given to patients.…”
Section: -6mentioning
confidence: 94%
See 2 more Smart Citations
“…Denture biofilm removal can be achieved via the application of different types of hygiene practices including mechanical methods, chemical agents and irradiation or combination of the aforementioned methods . Brushing represents the most commonly applied mechanical method combining the advantage of simplicity, effectiveness and low cost . Chemical cleansing methods can include a wide range of treatments: hypochlorites, peroxides, enzymes, acids, crude drugs and mouthwashes .…”
Section: Introductionmentioning
confidence: 99%